Effect of adenosine A1 receptor agonist on the enhanced excitability of spinal dorsal horn neurons after peripheral nerve injury. (1st March 2014) - Yamaguchi, Daisuke; Terayama, Ryuji; Omura, Shinji; Tsuchiya, Hiroki; Sato, Tadasu; Ichikawa, Hiroyuki; Sugimoto, Tomosada
<x xml:space="preserve">Abstract</x> Neuronal hyperactivity has been implicated in abnormal pain sensation following peripheral nerve injuries. Previous studies have indicated that the activation of adenosine A1 receptors (A1R) in the central and peripheral nervous systems produces an antinociceptive effect. However, the mechanisms involved in the peripheral effect are still not fully understood. The effects of the local application of the selective A1R agonist, 2-chloro-N(6)-cyclopentyladenosine (CCPA) on neuronal hyperactivity were examined in this study using a neuropathic pain model induced by a tibial nerve injury. We utilized Fos protein-like immunoreactivity induced by noxious heat stimulation to examine changes in the number of Fos protein like immunoreactive (Fos-LI) neuron profiles in the spinal dorsal horn, and behavioral analysis for mechanical and thermal sensitivities. The nerve injury induced an exaggerated Fos response to noxious heat stimulation. The number of Fos-LI neuron profiles was significantly decreased and their distribution was restricted to the central terminal field of the spared peroneal nerve 3 days after the injury. The number of Fos-LI neuron profiles returned to control levels and a large number of these profiles were observed in the central terminal field of the injured tibial nerve 14 days after the injury. These enhanced Fos responses were attenuated by the local application of CCPA. The nerve injury also resulted in mechanical allodynia and thermal hyperalgesia. The local application of CCPA inhibited thermal hyperalgesia, but was less effective against mechanical allodynia. These results indicated that activation of peripheral A1R plays a role in the regulation of nerve injury-induced hyperalgesia.